On the second spectrum of lattice modules - Phadatare Narayan; Ballal Sachin; Kharat Vilas (Discussiones Mathematicae - General Algebra and Applications, 2017)
The second spectrum Specs(M) is the collection of all second elements of M. In this paper, we study the topology on Specs(M), which is a generalization of the Zariski topology on the prime spectrum of lattice modules. Besides some properties, Specs(M) is characterized and the interrelations between the topological properties of Specs(M) and the algebraic properties of M, are studied.